Asianismus und Völkerrecht:: Japans sanfter Übergang von der Großostasiatischen Wohlstandssphäre zu den Vereinten Nationen, 1944–1956 - Zachmann, Urs Matthias (Comparativ, 2008)
Asianism and International Law: Japan’s Easy Transition from the Greater East Asia Co-Prosperity Sphere to the United Nations, 1944–56 Japan’s defeat in the Asian-Pacific-War (1937–45) is often seen as one of the great watersheds in global history. For Japan, it separates modern history from the present. However, there also existed conspicuous continuities, one of which was the seemingly easy transition from support of the wartime concept of a Greater East Asia Co-Prosperity sphere to the post-war international order centering on the United Nations. In international law, the transition was accomplished through the re-appropriation of legal concepts and political sentiments associated with the “Großraum”-concept of the Co-Prosperity Sphere and their transference to the new global peace order. This paper argues that the transference was made possible through an intrinsically integrative spirit, i.e. Asianism and internationalism, respectively, as the common link between the two seemingly contradictory concepts of international order.